2014
DOI: 10.1002/iub.1297
|View full text |Cite
|
Sign up to set email alerts
|

A review of starch‐branching enzymes and their role in amylopectin biosynthesis

Abstract: Starch-branching enzymes (SBEs) are one of the four major enzyme classes involved in starch biosynthesis in plants and algae, and their activities play a crucial role in determining the structure and physical properties of starch granules. SBEs generate a-1,6-branch linkages in a-glucans through cleavage of internal a-1,4 bonds and transfer of the released reducing ends to C-6 hydroxyls. Starch biosynthesis in plants and algae requires multiple isoforms of SBEs and is distinct from glycogen biosynthesis in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
135
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(139 citation statements)
references
References 71 publications
4
135
0
Order By: Relevance
“…These isoforms differ in their temporal expression, specificity, substrate specificity and product. (8)(9)(10)(11)(12)(13) While BEII isoforms tend to produce shorter chain branches with 6-7 glucose units, BEI favors the transfer of much longer oligomers with 14 to 70 units. (12,14,15) The isoforms of plant BEs are proposed to play distinct roles in the formation of the complex starch granule, at least in some species.…”
mentioning
confidence: 99%
“…These isoforms differ in their temporal expression, specificity, substrate specificity and product. (8)(9)(10)(11)(12)(13) While BEII isoforms tend to produce shorter chain branches with 6-7 glucose units, BEI favors the transfer of much longer oligomers with 14 to 70 units. (12,14,15) The isoforms of plant BEs are proposed to play distinct roles in the formation of the complex starch granule, at least in some species.…”
mentioning
confidence: 99%
“…Based on amino acid sequence relationships, SBEs are split into two classes, termed class I (B family) and class II (A family). A more general, comprehensive review of branching enzymes can be found elsewhere [274].…”
Section: Branch Linkage Formation By Starch Branching Enzymesmentioning
confidence: 99%
“…(Myers, Morell, James & Ball, 2000;Tetlow & Emes, 2014). There is also a very interesting alternative description by Bertoft and colleagues, e.g.…”
Section: Fitting the Amylopectin Number Cld With A Mathematical Modelmentioning
confidence: 96%